Metal Oxide Nanolayer-Decorated Epitaxial Graphene: A Gas Sensor Study - Rodner, Marius (Nanomaterials (Basel), 2020)
In this manuscript, we explore the sensor properties of epitaxially grown graphene on silicon carbide decorated with nanolayers of CuO, Fe(3)O(4), V(2)O(5), or ZrO(2). The sensor devices were investigated in regard to their response towards NH(3) as a typical reducing gas and CO, C(6)H(6), CH(2)O, and NO(2) as gases of interest for air quality monitoring. Moreover, the impact of operating temperature, relative humidity, and additional UV irradiation as changes in the sensing environment have been explored towards their impact on sensing properties. Finally, a cross-laboratory study is presented, supporting stable sensor responses, and the final data is merged into a simplified sensor array. This study shows that sensors can be tailored not only by using different materials but also by applying different working conditions, according to the requirements of certain applications. Lastly, a combination of several different sensors into a sensor array leads to a well-performing sensor system that, with further development, could be suitable for several applications where there is no solution on the market today.